Lamotrigine decreases MRP8 and IL-7 in rat models of intractable epilepsy secondary to focal cortical dysplasia - Wei, Jianping (Exp Ther Med, 2016)
The aim of the present study was to examine the effect of lamotrigine and the expression of myeloid-related protein 8 (MRP8) and interleukin-7 (IL-7) in the treatment of focal cortical dysplasia with secondary intractable epilepsy. In this study, rats with focal cortical dysplasia with secondary intractable epilepsy (constructed by our laboratory) were selected and used for experimentation, 21-day Sprague-Dawley rats were randomly divided into the control group (38 rats), the observation group I (39 rats), and the observation group II (38 rats). Rats in the observation group I received daily intraperitoneal injection of 0.02 mg/kg lamotrigine, and those in the observation group II and the control group received daily intraperitoneal injection of 0.02 mg/kg normal saline. Expression quantities of MRP8 and IL-7 in the hippocampus sample tissues of mice in the control group, observation group I, and observation group II were measured via fluorescence quantitative polymerase chain reaction assay, western blot analysis, enzyme-linked immunosorbent assay, and immunohistochemistry 48 h later. MRP8 and IL-7 gene mRNA levels of the control group, the observation group I and the observation group II had no significant differences (P>0.05). The expression quantity on the protein level of MRP8 and IL-7 showed no significant differences (P>0.05) between the observation group I (7.91±1.3, 3.86±0.38) and the control group (7.52±1.03, 3.62±0.29). The expression quantity of MRP8 and IL-7 showed significant differences (P<0.05) between observation group II (27.47±1.13, 19.45±0.48) and observation group I (7.91±1.3, 3.86±0.38). It was found that MRP8 and IL-7 were focused on the nerve cell membrane of hippocampus of rats in the observation group by immunohistochemistry experiments. In conclusion, the results from the present study show that lamotrigine can be used to treat rats with focal cortical dysplasia with secondary intractable epilepsy by reducing the expression levels of MRP8 and IL-7 in the body, providing a new therapeutic target to the follow-up treatment of focal cortical dysplasia with secondary intractable disease.